2011
DOI: 10.1111/j.1600-0404.2011.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Craniotomy for brain metastases: a consecutive series of 316 patients

Abstract: In this population study, the annual incidence of a first-time craniotomy for a brain metastasis was 2.6/100,000, the 30-day mortality rate was 3.8%, and median OS was 9.2 months. The well-known prognostic factors were confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…We observed a 30‐day post‐operative mortality rate of 4.3% for patients with cerebellar metastases, findings in accordance to our former series for brain metastases in general . This post‐operative mortality rate is higher than for craniotomies in general in our department , which may be due to the fact that some patients with brain metastasis have advanced extracranial disease at surgery.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We observed a 30‐day post‐operative mortality rate of 4.3% for patients with cerebellar metastases, findings in accordance to our former series for brain metastases in general . This post‐operative mortality rate is higher than for craniotomies in general in our department , which may be due to the fact that some patients with brain metastasis have advanced extracranial disease at surgery.…”
Section: Discussionsupporting
confidence: 90%
“…addressed cerebellar metastases as a highly significant negative prognostic marker for survival in multivariate Cox analysis for patients undergoing resection for melanoma, colorectal, and renal cancer metastases, albeit not significant for breast cancer . In our former consecutive series for intracranial metastases, we observed a median OS of 9.2 months for 316 patients with single or multiple lesions undergoing resection with or without post‐operative RT . Cerebellar tumor localization was in this cohort not a significant negative prognostic marker for OS in neither univariate ( P = 0.14) nor in multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[25][26][27]33 Surgical reports also highlight the importance of age, status of tumor, and performance rating to overall survival. 34,35 Few studies address the relative efficacy of surgical resection vs SRS even when WBXRT is administered. A multi-institutional observational study 7 reported that SRS was equivalent to resection for single brain lesions using earlier trials for comparison.…”
Section: Factors Related To Survivalmentioning
confidence: 99%